The role of phase I and II genetic polymorphisms, smoking, alcohol and cancer family history, in the risk of developing testicular cancer. Issue 7 (September 2019) - Roco, Angela; Lavanderos, Alejandra; Cayún, Juan P.; Acevedo, Cristian; Celedón, Cesar; Rubilar, Juan C.; Sandoval, Christopher; Cerpa, Leslie; García-Martín, Elena; Agúndez, Jose A.; Esguevillas, Gara; Amo, Gemma; et al.
Abstract : Background: Testicular cancer (TCa) is a malignant tumor with highest incidence and mortality rates in Chile. The genes coding for cytochrome P450, glutathione- S -transferases (GSTs), and UDP glucuronyl transferases (UGT) participate in the biotransformation and detoxification of xenobiotics. Mutations in these genes have been associated with a high incidence of various types of cancer and an increased risk of presenting adverse reactions to drugs. Objective: The aim of this study was to relate the presence of genetic polymorphisms in cytochrome P450 1A1 ( CYP1A1 ), CYP3A4, GSTM1, GSTP1, GSTT1, and UGT1A1 genes and nongenetic factors with the risk of developing TCa. Methods: A total of 276 volunteers from the Chilean general population and 251 Chilean TCa patients were recruited for the study. Genotypic analyses were performed using qPCR and PCR-RFLP. Results: Variant alleles found to increase the risk of developing TCa were CYP1A1*2C (rs1048943), GSTP1 (rs1695), and GSTT1null, especially when in conjunction with a cancer family history and/or a smoking habit. The results of the multivariate analysis showed that the presence of variant alleles of GSTP1 (rs1695) together with a smoking habit and a family history of cancer accounted for a 15.9% risk of developing TCa in the Chilean population. CYP1A1*2C, GSTM1null, GSTT1null, and GSTP1 (rs1695 ) are statistically related to the risk of appearance of TCa, alone or associated with nongenetic factors. Conclusion: Therefore, phase I and II variant alleles might be useful in evaluating susceptibility to TCa in the studied population.